Pemanfaatan Digital Marketing dalam Proses Pemasaran Produk Secret Garden Village: Utilization of Digital Marketing in the Marketing Process of Secret Garden Vilage Product - Manek, Angelica Graciela; Maheswari, Anak Agung Istri Agung (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The use of digital marketing has become an important strategy in product marketing to increase company profits and competitiveness. This article discusses the use of digital marketing in marketing Secret Garden Village products. The background to this research is the importance of digital marketing in the modern era which is supported by the rapid development of information and communication technology. This research aims to explore how the use of digital marketing can improve the marketing of Secret Garden Village products and expand market reach. The methodology used in this research is a case study with data collection through direct observation, interviews, and analysis of related documents. The research results show that the use of digital marketing in marketing Secret Garden Village products has succeeded in increasing brand awareness, increasing customer interaction, and increasing sales. In conclusion, the use of digital marketing can be an effective means for companies to reach a wider target market and get better profits. Therefore, companies should consider adopting digital marketing strategies in their product marketing efforts.